Sleight [videorecording (DVD)] - Dillard, J. D.; Latimore, Jacob, 1996-; Gabriel, Seychelle, 1991-; Hill, Dulé (Universal Pictures Home Entertainment, 2017)
Left to care for his little sister after their parents' passing, a young street magician turns to illegal activities to keep a roof over their heads. He is forced to use his magic and a brilliant mind to save his sister when he gets in too deep and she is kidnapped.